Comprehensive GC-MS Characterization and Histochemical Assessment of Various Parts of Three Colchicum Species from Bulgarian Flora - Ivayla Dincheva; Ilian Badjakov; Vasil Georgiev; Ivanka Semerdjieva; Radka Vrancheva; Ivan Ivanov; Atanas Pavlov (Plants)
This study presents a comprehensive phyto- and histochemical analysis of three Colchicum species: Colchicum autumnale L., the Balkan endemic Colchicum bivonae Guss., and the Bulgarian endemic Colchicum diampolis Delip. et Česchm. Using gas chromatography-mass spectrometry (GC-MS), 66 metabolites were identified, encompassing free amino, organic, phenolic, and fatty acids, sugars, and alkaloids, which were distributed among various plant parts. Organ-specific metabolic patterns revealed that corms and seeds are particularly rich in alkaloids, supporting their roles in chemical defense and survival during dormancy. Conversely, flowers, leaves, and capsules were enriched with energy-related and phenolic compounds, playing critical roles in reproduction and stress tolerance. Histochemical investigations localized alkaloids predominantly in the endosperm of seeds, parenchyma of corms, and vascular bundles of flowers. Notably, the endemic C. bivonae and C. diampolis displayed unique chemical profiles. Moderate acetylcholinesterase inhibitory activity (AChE) was observed across various plant organs. Statistical analyses demonstrated significant interspecies and organ-specific chemical differentiation, with certain metabolites serving as key markers. These findings enhance our understanding of the chemical composition, organ specialization, and potential as a source of new biomolecules in these Colchicum species. They underscore the ecological and pharmacological importance of endemic taxa and provide a framework for future research into their sustainable utilization and potential bioactivities.